Supercritical Fluid Evaluation and Extraction of Phenol from Sugarcane Bagasse Pyrolysis Oil (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a simple method to assess the cost of extracting group of phenols from bio-oil derived frompyrolysis of sugarcane bagasse and the incidental profits by employing by what has herein evolved as SupercriticalFluid Extraction (SFE) technology. Further, cost-cum-profit optimization has been done considering minimizationof batch time and enhanced purity as the contributive parameters based on experimental results. However, it isacknowledged that the solute extracted using supercritical carbon dioxide in this process is generally significantlydifferent from solute extracted using other conventional alternatives as regards both purity of, and components in,such other extracts. The extract obtained through SFE route deserves to be recognized as an updated, yet distinct,product vis-a-vis conventional/traditional extracts currently available commercially.